Essential earthbag construction : the complete step-by-step guide - Hart, Kelly, 1943- (Sustainable building essentials., 2018)
"Essential Earthbag Construction is an illustrated step-by-step guide to building primarily with earth-filled polypropylene bags, a low-impact, highly durable method with superior thermal mass and ease of construction. Coverage includes material specifications and use, building science, installation, design guidance, foundations, wall plastering, floors, roofs, and installing basic utilities, as well as seismic reinforcement, maintenance, remodeling, and the variety of uses."--